PATTERN OF RENAL PATHOLOGY IN FATAL VIPER BITE (DABOIA RUSSELLI): A MORTUARY BASED STUDY (Journal of Forensic Medicine & Toxicology, 2011)
Envenomation due to poisonous snakebite is a significant cause of mortality in India as well as other agrarian South East Asian countries. Renal failure is consider the leading mechanism of death in poisonous snakebite. Studies from India have shown snakebite (especially viper bite) as an important cause of acute renal failure necessitating the use of dialysis as life saving measure The present study was designed to explore the pattern of renal involvement in fatal cases and its association with type of snake. Autopsy study was conducted on a series of 36 fatal cases of snakebite during a two-year period The study involved complete medico legal autopsy and postmortem histological examination on cases at the mortuary of a tertiary care medical college and hospital The investigation revealed renal involvement in 77.8 % of the cases of fatal viper (Daboia russelli) bites. Acute cortical necrosis was the major type of lesion (72.2 %) followed by tubular necrosis.
Keywords: viper bite; renal pathology; lesion types; cortical necrosis; glomerulopathy; autopsy